Finite element analysis of 10 span beam bridge by using ANSYS - Tou, Shu Xian (2019)
Beam bridges are one of the most familiar used types of bridge as structurally they are simple to construct and maintain. Hence, they are preferred over other types of bridges when it comes to providing connectivity within short distance. In construction, engineer can link a number of spans of beam bridge together to create a longer bridge. In this study, the beam bridge was analyzed by using manual calculation and also design in ANSYS software. There are numerous methods can be used to analyses the behavior of the beam bridges. Nevertheless, among all these methods, finite element method and probabilistic method will be a very effective method used to obtain the strength and behavior of the beam bridges. The main purpose of this analysis is to determine the behavior of the beam bridge by using ANSYS software. The concrete grade of the section is HA35 and the reinforced steel used in the section is EHE S500. The values for the input variables are generated randomly by using Monte Carlo Simulation or as prescribed samples using Response Surface Methods. A total number of 1000 of simulations had been made to make sure the analysis is more precise and accurate. Through the stimulation, this study can prove that the condition of the beam bridge under the existence of randomness and uncertainty can be analyzed by apply probabilistic finite element analysis using ANSYS.